Implementasi Bantuan Sosial dari Pemerintah terhadap Kegiatan Filantropi Pada Masa Pandemi: Implementasi Bantuan Sosial dari Pemerintah terhadap Kegiatan Filantropi Pada Masa Pandemi - Versiandika Pratama; Fiona Kumalasari (Universitas Nahdlatul Ulama Sidoarjo, 2023)
This study aims to determine the implementation of social assistance provided by the government to the community towards philanthropic activities during the pandemic. This research belongs to qualitative research. The method in this research used descriptive analysis approach, with data collection techniques using interviews and direct observation. The results show that the emergence of corona has forced residents to save on expenses, including in philanthropic activities, however, residents can still provide social assistance, but not in large amounts. There is rationality infulfill life's needs and applying the concept of philanthropy during the pandemic along with changes in income, where the main priority remains to fulfill primary needs first, then the social needs of generosity can be carried out. Apart from that, the social assistance received from the government by the community, especially Kuripan Lor residents, can be said to be right on target and very helpful in meeting their daily needs. However, for philanthropic activities, residents are more satisfied with using personal money because they feel that there is a special sensation from the the activities he carries out to earn income can help other people's burdens.